The Analysis Study of Diagnosis and Management of Respiratory Distress Syndrome in Neonatus: A Comprehensive Systematic Review - Aldila, Raden Rara Farah; Erlich, Willyam Arnando Deggas (The International Journal of Medical Science and Health Research, 2024)
Background: Respiratory distress syndrome (RDS) management is crucial for preterm infants, as it aims to improve survival rates while minimizing the risk of adverse outcomes, particularly bronchopulmonary dysplasia (BPD). Methods: This systematic review exclusively examined full-text articles published in English between 2014 and 2024, adhering to the PRISMA 2020 guidelines. Result: The study conducted a thorough review of more than 4000 publications that were obtained from reputable databases, such as ScienceDirect, SagePub, and PubMed. Eight publications were identified as necessitating a more comprehensive examination subsequent to an initial screening. As a result, a comprehensive review of these selected studies was conducted to guarantee an exhaustive and rigorous assessment. Conclusion: RDS diagnosis and management differ significantly between Japan and Europe, with neonatologists administering surfactants based on confirmed diagnosis rather than FiO2 levels. In Japan, chest radiography and stable microbubble rating are commonly used diagnostic tools, but accuracy can be influenced by variability and sample contamination. Challenges remain in distinguishing RDS from transient tachypnea.